Cover. Issue 12 (17th December 2022) - Farrell, Timothy W.; Hung, William W.; Unroe, Kathleen T.; Brown, Teneille R.; Furman, Christian D.; Jih, Jane; Karani, Reena; Mulhausen, Paul; Nápoles, Anna María; Nnodim, Joseph O.; Upchurch, Gina; Whittaker, Chanel F.; et al.
Abstract : Intersection of Ageism and Racism in Healthcare: A Double Disadvantage. See the related article by Farrell et al., pages 3366‐3377 .